2010
DOI: 10.1111/j.1742-7843.2009.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Iron(III) Reduces Phosphorus Levels in Alloxan Diabetes‐Induced Rats with Signs of Renal Failure Development

Abstract: This study evaluates the effect of complex cross-linked chitosan iron-(III) (CH-FeCL) polymer as phosphate binder in renal failure induced by alloxan (150 mg/kg, i.p.) in rats. The animals (male and female) were divided into four groups and received the treatment once a day for 15 days: (i) control group, which received a single injection of saline (3 ml/kg, i.p.) and normal diet; (ii) alloxan group, which received only a dose of alloxan and normal diet; (iii) phosphate (PO4) group, which received diet supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The cross‐linking process with glutaraldehyde renders the polymer insoluble at the acidic pH in the stomach, preventing the release of iron , which, as a transition metal, can establish a strong link to phosphate. The phosphate‐chelating capacity of this non‐absorbable polymer was demonstrated in previous animal and in vitro studies, with a serum phosphate reduction of 20%–40%, without promoting changes in serum iron levels . However, although these animals presented elevated phosphate levels, they did not develop CKD, contrary to the animals in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross‐linking process with glutaraldehyde renders the polymer insoluble at the acidic pH in the stomach, preventing the release of iron , which, as a transition metal, can establish a strong link to phosphate. The phosphate‐chelating capacity of this non‐absorbable polymer was demonstrated in previous animal and in vitro studies, with a serum phosphate reduction of 20%–40%, without promoting changes in serum iron levels . However, although these animals presented elevated phosphate levels, they did not develop CKD, contrary to the animals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…CH‐FeCl combines the chelation properties of chitosan and iron, without the risk of increased iron availability and consequent toxicity. This compound has been shown to reduce phosphate absorption in the intestine of diabetic rats with hyperphosphataemia induced by diet phosphorus overload . However, in those studies, the animals did not have CKD or CKD‐MBD, which limits the clinical usefulness of the results.…”
mentioning
confidence: 99%
“…17 Previous in vitro and in vivo studies with diet phosphorus overload models have shown the efficacy of iron-III chitosan (Ch-Fe(III)CL) as a chelator. [17][18][19] However, the phosphorus-chelating effect of Ch-Fe(III)CL in VC has not yet been tested in a model of CKD-induced hyperphosphatemia.…”
Section: Impact Statementmentioning
confidence: 99%
“…This product was then added to a 15% glutaraldehyde solution in acetone (Merck, Cotia, Brazil) for 24 h, filtered and washed with water to remove excess glutaraldehyde. [17][18][19] All drugs were dissolved in distilled water.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Fermagate (iron-Mg hydroxycarbonate), SBR-759 (a polymeric complex of iron and starch), PT-20 (ferric-hydroxide adipate) and cross-linked chitosan iron-(III) are currently in different phases of development 57,112,114,129 . Old papers reported that iron-dextran, iron-hydroxide, and iron-saccharide also bind P effectively 57 .…”
Section: Other Iron-based P-bindersmentioning
confidence: 99%